Framing Cultural Identity and Space through Translation: The Case of Shulamis Yelin's Fiction - Spoturno, María Laura (2010)
The overall aim of this paper is to approach the question of linguistic and cultural translation and its influence on the configuration of distinctive cultural spaces in Yelin's collection Shulamis. Stories from a Montreal Childhood. The main character of this collection struggles between worlds -which are, to a certain extent, symbolised by the use and allusion to English, Yiddish and French- in search of her own linguistic and cultural identity. Thus, the confrontation of different spaces and the need to translate one's experience becomes a significant element in Yelin's writing. The stories in this collection present Canada's spirit of respect and equitable treatment for all cultures and identities while showing the difficulties immigrants had to face as well as the dangers of acculturation. In this paper, we examine the construction of different cultural spaces from a theoretical perspective which considers the importance of some cultural and linguistic processes associated with code-switching (Poplack, 1984, Myers-Scotton, 1993, 2006), giving due attention to the phenomena of linguistic and cultural translation (Bhabha, (1994) 2006, Tymoczko, 2000, Trivedi, 2005). Also, we look at the position of Shulamis Yelin as a writer who wishes to translate worlds for her readers.